1994
DOI: 10.1002/rrr.3450090105
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of river regulation on mammals and birds: A review

Abstract: Although most of the world's river systems are regulated, the effects of river regulation on mammals and birds are little known. In fact, speculations are more common than empirical data. A review of this topic is presented, emphasizing northern rivers where most impacts have been described. Effects are related to the major causes of change. It is concluded that the two most disastrous effects of river regulation on mammals and birds are the permanent inundation of vast areas of land, and the disruption of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…After the closure of the High Aswan dam in the mid-1960s, the discharge of the Nile River during the annual fl ood period decreased by around tenfold (Tockner and Stanford 2002 ) with severe consequences for fl oodplain and estuary areas, even affecting marine fi sheries in the Eastern Mediterranean (White 1988 ). Elimination of fl oods reduces the lateral connectivity of river systems, often precluding the inundation of fl oodplains that are critical habitats for the reproduction of several aquatic and semiaquatic organisms (Nilsson and Dynesius 1994 ;FitzHugh and Vogel 2011 ). The impact of fl ow regulation extends beyond quantity of water and also affects water quality.…”
Section: Flow Regulation and Ecosystem-level Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the closure of the High Aswan dam in the mid-1960s, the discharge of the Nile River during the annual fl ood period decreased by around tenfold (Tockner and Stanford 2002 ) with severe consequences for fl oodplain and estuary areas, even affecting marine fi sheries in the Eastern Mediterranean (White 1988 ). Elimination of fl oods reduces the lateral connectivity of river systems, often precluding the inundation of fl oodplains that are critical habitats for the reproduction of several aquatic and semiaquatic organisms (Nilsson and Dynesius 1994 ;FitzHugh and Vogel 2011 ). The impact of fl ow regulation extends beyond quantity of water and also affects water quality.…”
Section: Flow Regulation and Ecosystem-level Impactsmentioning
confidence: 99%
“…The loss of terrestrial habitat affects valley bottoms especially, which are the most productive environments in many areas (e.g. mountains, high latitudes) and often host diverse and abundant biological communities (Nilsson and Dynesius 1994 ;Nilsson and Berggren 2000 ). The new water masses can also constitute effective barriers precluding the movement of terrestrial species and disrupting migration behaviors (Nellemann et al 2003 ).…”
Section: Upstream Habitat Modifi Cationsmentioning
confidence: 99%
“…The most negative downstream consequence of river regulation on mammals and birds is the disruption of the seasonal flood regime along the river (Nilsson & Dynesius, 1994). In the long term, reduced flooding can alter vegetation communities that may be important for a wide range of mammal and bird species.…”
Section: Impacts On Birds and Mammalsmentioning
confidence: 99%
“…At the Fortuna dam in Panama, a 10 km 2 reservoir is surrounded by a 160 km 2 nature reserve. This limits erosion and reduces sediment deposition in the reservoir (Leibenthal, 1997) Oulujarvi, a regulated lake in Finland, is drawn down to reduce the erosion of sandy shores caused by spring floods (Hellesten, 1996) Sediment flushing of the Hengshan reservoir in China, for a few weeks every 2 -3 years, enables the long-term capacity of the reservoir to be maintained at 75% of the original capacity (Atkinson, 1996) Terrestrial wildlife Wildlife rescue 10,000 animals were rescued from drowning prior to the filling of the Afokaba reservoir on the Surinam River in South America (Nilsson & Dynesius, 1994) Enhancement of reservoir islands for conservation Outlet works aeration In the USA, Duke Power has experimented with various approaches to increase dissolved oxygen levels in turbine tailraces. At the Wateree Dam, turbine blades were modified to enable air to be drawn into the water through small holes in the turbine vanes.…”
Section: Options For Environmental Protectionmentioning
confidence: 99%
“…Other studies have shown the harmful effects of altering flow by constraining rivers with artificial levees, dikes or groynes (e.g. reviews in Nilsson & Dynesius, 1994;Nilsson & Berggren, 2000). However, most of these studies have focused on floodplain habitats (marshes, riparian forests, etc.)…”
Section: Introductionmentioning
confidence: 99%